2017
DOI: 10.1111/ijfs.13351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum‐drying, hot air‐drying and freeze‐drying on polyphenols and antioxidant capacity of lemon (Citrus limon) pomace aqueous extracts

Abstract: Summary The aim of this study was to investigate the effect of freeze‐drying, hot air‐drying and vacuum‐drying at 70, 90 and 110 °C, on dried lemon pomace polyphenols and antioxidant capacity. The total phenolic content and antioxidant capacity were higher in lemon pomace dried by hot air or under vacuum than those dried by freeze‐drying and increased as the temperature increased. The highest total flavonoid content was recorded in the pomace dried under vacuum at 70 and 90 °C. Lemon pomace dried by freeze‐dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 25 publications
13
74
0
1
Order By: Relevance
“…In summary, the levels of TPC, flavonoids and saponins as well as antioxidant capacity of S. spinescens samples were generally increased as the temperature of the vacuum oven drying was increased. These findings are consistent with that of Papoutsis et al () who found that antioxidant capacity increased with temperature up to 120°C in lemon peels. The vacuum drying conditions of 90°C for 6 hr had the highest levels of TPC, flavonoids and saponins as well as antioxidant capacity; therefore, these conditions were selected for direct comparison of energy usage with the other drying methods (Table )…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In summary, the levels of TPC, flavonoids and saponins as well as antioxidant capacity of S. spinescens samples were generally increased as the temperature of the vacuum oven drying was increased. These findings are consistent with that of Papoutsis et al () who found that antioxidant capacity increased with temperature up to 120°C in lemon peels. The vacuum drying conditions of 90°C for 6 hr had the highest levels of TPC, flavonoids and saponins as well as antioxidant capacity; therefore, these conditions were selected for direct comparison of energy usage with the other drying methods (Table )…”
Section: Resultssupporting
confidence: 93%
“…The drying process can lead to the degradation of bioactive compounds, especially if the compounds are heat‐sensitive (Nguyen et al, ; Nguyen, Van Vuong, Bowyer, Van Altena, & Scarlett, ; Ning, Lee, & Han, ; Vu et al, ). However, the drying process, often involving increased temperatures, can also release bound compounds resulting in higher recoveries upon extraction (Nindo, Sun, Wang, Tang, & Powers, ; Papoutsis et al, ; Sharma et al, ; Wojdyło, Figiel, & Oszmiański, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the total polyphenol content was higher than the results reported by Li et al [25] and similar to the values obtained by Wang et al [26] in citrus residues; in both cases, they used methanol as an extraction solvent. However, the TPC value was lower than the values mentioned by Papoutsis et al [27]; this can be explained due to the different conditions used by these authors for drying peel preparation prior to TPC extraction with hot water, furthermore, the species of the citrus residue evaluated was also different (C. limon). Additionally, in our case, a lower TPC content could also be attributed to a previous essential oil extraction that could take part of the polyphenols presents in the peel and increase polyphenolic degradation before flour preparation.…”
Section: Tpc Antioxidant Activity and Polyphenol Profilementioning
confidence: 56%
“…Lemon waste including peel, membranes and seeds was kindly provided by a commercial juicing factory in Kulnura, NSW, Australia. After seed removal, the remaining peels and membranes with a moisture content of 85 AE 1% (mean AE standard deviation) were freeze-dried for 48 h as described by Papoutsis et al (2017). The dried by-product was then ground using a commercial blender (Waring 2-speed blender, John Morris Scientific, Chatswood, Australia), and the powder passed through a 1.40-mm mesh sieve (EFL 2000; Endecotts Ltd., London, England) was used for the extraction.…”
Section: Methodsmentioning
confidence: 99%
“…A large amount of citrus by-products are annually generated by the juice industry and are a good source of polyphenols (Papoutsis et al, 2017;Sharma et al, 2017). Phenolic compounds of citrus peels include phenolic acids (Ma et al, 2008) and flavonoids which are usually found in conjugated forms (Bilbao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%